Association of impaired pulmonary function and objectively measured physical activity in a population study - Maria Lopmeri; Tiina Mattila; Kari Tokola; Tommi Vasankari; Tuija Jääskeläinen; Jouni Lahti; Tuula Vasankari (Scientific Reports)
Abstract Due to modern lifestyles, physical activity (PA) has decreased at a population level, resulting in health concerns worldwide. Increased level of PA can reduce mortality and morbidity in pulmonary diseases, such as asthma and chronic obstructive pulmonary disease (COPD). Many previous studies on the association between pulmonary function and PA assessed PA by questionnaires. We aimed to study the cross-sectional association between pulmonary function and objectively measured PA and sedentary behavior (SB) in population-based data. A total of 4729 subjects participated in the Health 2011 survey, which represents the Finnish adult population. Of these, 1511 completed spirometry and the required 4-day accelerometer wear time. Spirometry values of forced expiratory volume in 1s (FEV1) and forced vital capacity (FVC) were determined. We compared the differences in daily PA measured with triaxial accelerometer between those with obstructive or restrictive spirometry results (defined as FEV1/FVC < −1.65 z-score, lower limit of normal [LLN] and FVC < −1.65 z-score, respectively) and those with FEV1 < −1.65 z-score to those with normal spirometry in adjusted logistic regression analysis. Airway obstruction, pulmonary restriction, and FEV1 < LLN were associated with less time spent in moderate (adjusted odds ratio [OR] 0.63, 95% confidence interval [CI] 0.40-0.99; OR 0.65, 95% CI 0.43–1.00; OR 0.58, 95% CI 0.39–0.87, respectively) and moderate-to-vigorous level of PA (OR 0.65, 95% CI 0.43–0.98; OR 0.63, 95% CI 0.42–0.94; OR 0.56, 95% CI 0.38–0.82, respectively). Those with restrictive spirometry had greater time spent sedentary and a lower daily step count when compared to those with normal spirometry. Respective ORs with 95% CIs were 1.09 (1.01–1.19) and 0.85 (0.75–0.96). Our results show the association between impaired pulmonary function and measured lower level of daily PA. Restriction associated with greater time spent sedentary and a lower daily step count when compared with those with normal spirometry, airway obstruction, and FEV1 < LLN.